Respuesta :
Answer:
A) 6x - 27
Step-by-step explanation:
Given expression:
[tex]-9(x + 3) + 15x[/tex]
Apply the distributive property:
[tex]\implies -9 \cdot x -9 \cdot 3+15x[/tex]
[tex]\implies -9x -27+15x[/tex]
Collect like terms:
[tex]\implies -9x+15x -27[/tex]
Combine like terms:
[tex]\implies 6x -27[/tex]
Answer:
[tex] \sf \: a) \: 6x - 27[/tex]
Step-by-step explanation:
Now we have to,
→ simplify the given expression.
The expression is,
→ -9(x + 3) + 15x
Let's simplify the expression,
→ -9(x + 3) + 15x
→ -9x - 27 + 15x
→ (-9x + 15x) - 27
→ (6x) - 27
→ 6x - 27
Hence, the answer is 6x - 27.